Pengaruh E-resources Dan Literasi Informasi Terhadap Kompetensi Lulusan Magister (S2) - Anton Risparyanto (Direktorat Perpustakaan Universitas Islam Indonesia, 2023)
In order to develop and manage science and technology as well as research, the competence of Masters graduates (S2) can be increased through the availability of e-resources collections in the library and students' information literacy skills. The problem of the influence of collection of e-resources and information literacy on the competence of Master graduates (S2) needs to be done with the aim of knowing: 1) The high value of e-resources, information literacy and competence of Master graduates (S2). 2) The relationship between e-resources and information literacy and 3) The significant value and influence of e-resources and information literacy on the competence of Master graduates (S2) partially or simultaneously. This quantitative research consists of 2 independent variables, namely e-resources and information literacy with the dependent variable competence of Masters graduates (S2) with the number of samples taken by probability sampling. Data were analyzed with multiple linear regression, F test method, t test and determinant test (R2). The results of the study can be concluded that the availability of electronic resources (e-resources) has a significant relationship with information literacy skills. This relationship alone (partially) has a significant effect on making a relative contribution to the competence of Master graduates (S2). Likewise simultaneously (simultaneously) has a significant influence in making an effective contribution to the competence of Masters graduates (S2) by 13.1%.